2008
DOI: 10.1016/j.ajo.2007.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year Follow-up of Photorefractive Keratectomy for Myopia of Less Than −6 Diopters

Abstract: Photorefractive keratectomy for myopia of less than -6 D is a safe and effective procedure in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 27 publications
3
42
2
2
Order By: Relevance
“…Despite the fact that many papers have been published, few studies have reported the long-term outcome of PRK over more than 10 years [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…Despite the fact that many papers have been published, few studies have reported the long-term outcome of PRK over more than 10 years [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 96%
“…Cornea laser refractive surgery has become generally accepted as a safe approach for correcting low-to-moderate refractive errors, and satisfactory visual acuity outcomes have been widely reported (1) . Nevertheless, the quality of vision may be altered due to changes in contrast sensitivity, glare, and/or higher-order aberrations (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have performed retouches to the surface ablation without MMC, and found no significant incidence of postoperative haze in the treatment of residual myopia. (31,32) However, the tendency to develop haze is directly proportional to the number of retreatments. Several studies have reported post-operative opacity in eyes that had PRK and subsequent LASIK without the use of MMC.…”
Section: As Adjuvant Therapy After Prkmentioning
confidence: 99%